Kemampuan Guru dalam Pengelolaan Manajemen Kelas pada Pembelajaran Efektif di Kelas V SDN 060858 Durung - Mutia Ramadhani; Domi Yanti Sinaga; Nia Febrianty Purba; Isma Novia Siregar; Rendi Irwansyah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to evaluate teachers' competence in managing classroom management to create a more optimal learning process in Grade V at SDN 060858 Durung. The study employs a qualitative approach with data collection methods including interviews, observations, and documentation. The findings reveal that effective classroom management plays a crucial role in improving the quality of learning. This is reflected in a well-organized classroom environment and active student participation in the learning process. However, several challenges in classroom management remain, such as the implementation of conventional teaching methods that are less engaging and a teaching style that tends to be authoritarian, which negatively impacts students' motivation and discipline. To address these issues, innovations in learning strategies are necessary, such as implementing an inquiry-based learning model that can enhance critical thinking skills, increase students' interest in learning, and deepen their understanding of the material. Additionally, teachers are encouraged to strengthen character education to instill discipline and a sense of responsibility among students within the school environment.